Human Genetic Variations Associated with Periodontitis- A Mini Review - V, NANCY SELVAMARY; J, VIJAYASHREE PRIYADHARSINI; AS, SMILINE GIRIJA (The journal of contemporary issues in business and government, 2021)
Periodontitis (PD) is a complex, multifactorial disease which involves participation of microbial and host factors. Microbes activate inflammatory response in the host which stimulates the periodontal cells to secrete metalloproteinases and other proteolytic enzymes eventually resulting in the tissue destruction and bone resorption. Numerous experimental reports have gathered information related to the potential biomarkers involved in PD. Genetic component of the host as well as the microorganism has been shown to play a pivotal role in the pathogenesis of the disease. Human genetic variation is considered to be a susceptibility factor in relation to PD. These variations could make an individual resistant or susceptible to infections caused by the microorganisms. Also, other factors such as food habits, lifestyle, smoking, alcoholism and poor oral hygiene practice can aggravate the disease. The magnitude of the disease PD that a patient develops is due to factors related to the individual’s response to the bacterial colonization. Several inflammatory markers and the genes encoded by them are discussed in the present review. Thus the review provides a general overview of the genes and their proteins in association with different forms of PD.